God’s vengeance… to wipe away the tears of the oppressed: a reading of 1Revelation 6:10 (2017)
In times of crisis and conflict, when injustice and impunity cast a pall over the land, Christians can experience a common feeling: the wish that God intervene in history and bring justice, which does not seem to come through human efforts alone. However, this longing for justice can hide a certain desire for revenge. That is the feeling of the slaughtered people of Revelation 6:10 who cry out to God for revenge. This article proposes, from the analysis of the biblical book, that the way that God responds to the victims’ clamor of vengeance is not by attacking the oppressors but by wiping away the tears of the oppressed, giving them consolation and comfort. From the point of view of the relationship between orthopraxis and orthodoxy, it implies that, by the ecclesial community, assume as a first response this way of God’s acting, that is to say, to offer effective comfort and relief to victims.